The Influence of E-Learning Implementation and The Quality of Virtual Interaction as Determining Factors of Student Learning Satisfaction - William Wun; Reni Silviah (International Journal of Advanced Multidisciplinary, 2026)
Literature Review of the influence of E-Learning implementation and the quality of virtual interactions as determining factors of student learning satisfaction is a scientific article with the aim of analyzing whether the implementation of E-Learning and the quality of virtual interactions affect student learning satisfaction. This research method uses a literature review method by examining national and international journal articles relevant to the implementation of E-Learning, the quality of virtual interactions, and student learning satisfaction. The results of this article are: 1) E-Learning implementation affects student learning satisfaction; 2) The quality of virtual interactions affects student learning satisfaction. Apart from these 2 exogenous variables that affect the endogenous variable, namely student learning satisfaction, there are still many other factors including learning facilities, lecturer performance, technological readiness.